Two new species of Empis (Diptera: Empididae) from Turkey - Çi̇ftçi̇, Mustafa Cemal; Hasbenli̇, Abdullah; Canpolat, Derya (Zootaxa, 2012)
The Turkish fauna of the genus Empis is poorly known, with only 45 species listed in the literature. Two new species,Empis (Polyblepharis) nabucco Çiftçi sp. nov. and Empis (s.str.) doronicola Çiftçi sp. nov. are described from mountainsof central Turkey. Both sexes are described and compared with related species. Male genitalia, and also mid leg of Empis (s.str.) doronicola Çiftçi sp. nov. are illustrated. Keys to Turkish species of Empis (s.str.) and E. (Polyblepharis) are given.